1991
DOI: 10.1159/000170010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro Production of Tumour Necrosis Factor by Monocytes in Dialysis Patients

Abstract: Modification of the cellular immune response in uraemia is partly responsible for the increased susceptibility to infection found in dialysis patients. In order to study this further we have evaluated the in vitro production of tumour necrosis factor (TNF) by peripheral-blood monocytes (PBMCs) to stimulation by lipopolysaccharide (LPS) from dialysis patients with end-stage renal failure. The patients were subdivided into two groups according to the type of dialysis: those undergoing haemodialysis (HD; n ≈ 12) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
4
1
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
8
4
1
1
Order By: Relevance
“…In contrast to several other reports we did not find any significant difference in the amount of LPS-induced TN Fa activity between the HD groups and the controls [29][30][31]. There are several possible explanations for this discrep ancy.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to several other reports we did not find any significant difference in the amount of LPS-induced TN Fa activity between the HD groups and the controls [29][30][31]. There are several possible explanations for this discrep ancy.…”
Section: Discussioncontrasting
confidence: 99%
“…We confirmed our previous observations as well as those of others [17][18][19] that both pre-and post-HD PBMC produced significantly more TN Fa activity than the PBMC of normal controls. In addi tion we found that PBMC from HD patients produced significantly more TN Fa than PBMC from uremic patients not on dialysis who had TN Fa activity similar to that of controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar results were obtained for TNF [102,103] and IL-6 [104,105]. An IL-6 production (related to beta-2-microglobulin release) was observed, by our group, both before and after dialysis treatment with cellulosic membranes, suggesting a chronic or prolonged PBMC stimulation [106].…”
Section: Cytokine Production By Cultured Pbmcsupporting
confidence: 80%